Tolerance of T2 Generation ‘Kitaake’ Rice (Oryza sativa L.) CRISPR/Cas9-OsGA20ox-2 Mutant Strains to Drought Condition - Husni Mubarok; Panjisakti Basunanda; Tri Joko Santoso (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Rice (Oryza sativa L.) is important staple crop in Indonesia. Food demand that continues to rise while inadequate land could be managed by assembling superior cultivar using CRISPR-Cas9 system method. Editing the genome by mutating the GA20ox-2 gene could improve both crop yield and ability to thrive in marginal land (drought). This experiment aims to obtain non-transgenic mutant plants (non Cas9 and hpt genes), gain information on GA20ox-2 gene expression levels, and study the tolerance levels of the CRISPR /Cas9-OsGA20ox-2 mutant lines 'Kitaake' T2 generation against drought conditions. Planting material using a mutant gene GA20ox 2 ‘Kitaake’ (K23.1, K15, K29.1, K19.1) and wild-type comparison. From 20 plants, respectively the K23.1, K15, K29.1, and K19.1 lines have 50%, 50%, 0%, and 45% of non-transgenic plants. DNA mutations in the form of deletion 44 bases (K23.1, K29.1, K19.1) and insertion of two bases (K15) are transcribed into RNA. The transcription results in a number of lower amino acids compare to its wild type (389 amino acids). The lines K23.1, K29.1, K19.1 have 373 amino acids and the K15 line has 300 amino acids (frameshift). Differences in the number of amino acids result in different phenotypic expressions. K15 mutant line has lower plant height and leaf length than the other mutant lines and wild type. The decrease does not decrease the potential of the crop. Mutations in the K15 line did not indicate better tolerant response to drought stress than other mutant lines and wild type in both vegetative and generative phase.